An Efficient Synthesis of 2-(Trifluoromethyl)-2H-[1,3]oxazino[2,3-a]isoquinolines via a Three-Component Cascade Approach Using a Continuous-Flow Microreactor - Lei, Ming; Tian, Wan; Hu, Ruijun; Li, Wei; Zhang, Hong (Synthesis, 2012)
The three-component reaction between an isoquinoline, a dialkyl acetylenedicarboxylate and 2,2,2-trifluoro-1-phenylethanone involving a 1,4-dipolar cycloaddition cascade approach is developed using a continuous-flow microreactor. The reaction conditions (solvent, flow rate and temperature) are optimized leading to the synthesis 2-(trifluoromethyl)-2H-[1,3]oxazino[2,3-a]isoquinoline derivatives in 79-83% isolated yields, whilst eliminating the formation of 11bH-pyrido[2,1-a]isoquinoline-1,2,3,4-tetracarboxylate by-products. The continuous-flow method is also applied to similar reactions using aromatic aldehydes as the carbonyl component.
Keywords: multicomponent reactions; microreactor; 1,4-dipolar cycloaddition; continuous-flow system; 2-(trifluoromethyl)-2H-[1,3]oxazino[2,3-a]isoquinolines